Analisis Pemikiran Kritis Imam Al-Suyūṭī terhadap Hadis Al-Takbīr Jazm dalam Kitab Al-Ḥāwī Li Al-Fatāwā - Zahri, Ahmad Fauzan; Muhid, Muhid; Nabilah, Is'ad Durrotun; Nurita, Andris; Ilmi, Moh. Hudal Hafid (el Buhuth: Borneo Journal of Islamic Studies, 2024)
This study aims to discuss the critical thinking of Imam al-Suyūṭī regarding the hadith with the wording “al-takbīr jazm” in the book al-Ḥāwī li al-Fatāwā. Imam al-Suyūṭī in his book, al-Ḥāwī li al-Fatāwā, criticizes a hadith that reads “al-takbīr jazm” (takbir is jazm/sukūn). The criticism includes the authenticity and understanding of other scholars regarding the hadith. This study uses a qualitative research method with a type of library research and a character study approach from Abdul Mustaqim. The main source in this research is the book al-Ḥāwī li al-Fatāwā by Imam al-Suyūṭī. The result of this study is that Imam al-Suyūṭī said that the hadith “al-takbīr jazm” did not come from the Prophet, but from the words of Ibrāhīm al-Nakha‘ī who was a tabiin. Imam al-Suyūṭī also criticized some interpretations of scholars who interpreted the word jazm by not lengthening the reading (madd) and removing the harakat at the end of the word (not inflected for i‘rāb). According to Imam al-Suyūṭī, the meaning of the word jazm is only not lengthening the reading (madd), and does not include the removal of the harakat at the end of the word (not inflected for i‘rāb). Nonetheless, the recitation of jazm in takbir is not a condition of the validity of the prayer and does not have serious implications if left out, because reciting takbir with jazm is sunnah.